9
$\begingroup$

Let $a_{1}, \cdots, a_{n}$ and $b$ be real numbers. I like to know the determinant of the matrix $$\det\begin{pmatrix} a_{1}+b & b & \cdots & b \\ b & a_{2}+b & \cdots & b \\ \vdots & \vdots & \ddots & \vdots \\ b & b & \cdots & a_{n}+b \end{pmatrix}=?$$ I guess the answer is $$a_{1} \cdots a_{n}+ \sum_{i=1}^{n} a_{1} \cdots a_{i-1} b a_{i+1}\cdots a_{n} $$ after some direct calculations for $n=2,3$. The question is how to calculate it for general $n$. Thanks!

$\endgroup$
2
  • 2
    $\begingroup$ Maybe induction? $\endgroup$ – Arpan Apr 24 '15 at 7:15
  • 3
    $\begingroup$ Subtract the first row from each of the others, looks like you get a matrix that should be easier to deal with as it's mostly zeros. $\endgroup$ – Gerry Myerson Apr 24 '15 at 7:22
6
$\begingroup$

Use the formula $\det(I+AB)=\det(I+BA)$.

First suppose $\Lambda = \operatorname{diag}(a_1,...,a_n)$ is invertible (that is, all the $a_k$ are non zero).

Then the matrix above can be written as $b e e^T + \Lambda = \Lambda (b \Lambda^{-1} e e^T + I)$, where $e = (1,...1)^T$. Then $\delta = c = \det \Lambda \det (\Lambda^{-1} e e^T + I) = \det \Lambda (1+b e^T \Lambda^{-1} e) $.

Expanding gives $\delta = (\prod_k a_k) (1 + b \sum_k {1 \over a_k})= \prod_k a_k + b \sum_k \prod_{i \neq k} a_i$.

Continuity shows that the formula holds for all $a_n$.

Addendum:

The functions $f_1(a) = \det(b e e^T + \operatorname{diag}(a_1,...,a_n))$, $f_2(a) = \prod_k a_k + b \sum_k \prod_{i \neq k} a_i$ are both continuous and defined for all $a$. We have shown above that $f_1(a) = f_2(a)$ for all $a$ such that no component of $a$ is zero.

Suppose $a$ is arbitrary, then there are $a_k \to a$ such that all components of $a_k$ are non zero. Continuity shows that $f_1(a) = f_2(a)$.

$\endgroup$
6
  • $\begingroup$ "Continuity"? Maybe you meant "induction"? $\endgroup$ – Timbuc Apr 24 '15 at 7:40
  • $\begingroup$ No, I meant continuity. There is no explicit induction in my answer. $\endgroup$ – copper.hat Apr 24 '15 at 7:40
  • $\begingroup$ Ok...continuity of what in what topological space? Thanks. And there's still "hidden" induction. $\endgroup$ – Timbuc Apr 24 '15 at 7:41
  • $\begingroup$ Thanks. The condition of a_k non-zero is ok to me. $\endgroup$ – user223515 Apr 24 '15 at 7:44
  • $\begingroup$ @Timbuc: $\mathbb{R}^n$ using the usual topology. If you accept the formula $\det(I+AB) = \det(I+BA)$ there is no induction. $\endgroup$ – copper.hat Apr 24 '15 at 7:46
5
$\begingroup$

My solution is less elegant, but only involves basic properties of the determinant. Since the determinant is invariant under column operations, you have

$$\Delta := \det\begin{pmatrix} a_{1}+b & b & \cdots & b \\ b & a_{2}+b & \cdots & b \\ \vdots & \vdots & \ddots & \vdots \\ b & b & \cdots & a_{n}+b \end{pmatrix}= \det\begin{pmatrix} a_{1} & 0 & 0 & \cdots & b \\ -a_2 & a_{2} & 0 & \cdots & b \\ 0 & -a_{3} & a_3 & \cdots & b \\ \vdots & \vdots &\vdots & \ddots & \vdots \\ 0 & 0 & 0 &\cdots & a_{n}+b \end{pmatrix},$$

by subtracting the second column from the first, the third column from the second, ...

Using Laplace expansion of the last column you get

$$ \Delta = \sum_{k=1}^{n-1} \left[(-1)^{n+k}b\right] \left[\prod\limits_{i=1}^{k-1} a_i \right] \left[\prod\limits_{i=k+1}^n (-1)a_i \right] + (a_n+b) \left[\prod\limits_{i=1}^{n-1} a_i \right]. $$

Simplifying the first summand yields

$$ \Delta = \sum_{k=1}^{n-1} \left[(-1)^{n+k}(-1)^{n-k}b\right] \prod\limits_{\substack{i=1\\i\neq k}}^{n} a_i + (a_n+b) \prod\limits_{i=1}^{n-1} a_i, $$

Which finally gives the desired formula

$$ \Delta = b \sum_{k=1}^{n} \prod\limits_{\substack{i=1\\i\neq k}}^{n} a_i + \prod\limits_{i=1}^{n} a_i. $$

$\endgroup$
1
$\begingroup$

Applying multilinearity and an inductive argument:

$$\begin{vmatrix} a_{1}+b & b & \cdots & b \\ b & a_{2}+b & \cdots & b \\ \vdots & \vdots & \ddots & \vdots \\ b & b & \cdots & a_{n}+b \end{vmatrix}=\begin{vmatrix} a_{1} & b & \cdots & b \\ 0 & a_{2}+b & \cdots & b \\ \vdots & \vdots & \ddots & \vdots \\ 0 & b & \cdots & a_{n}+b \end{vmatrix}+\begin{vmatrix} b & b & \cdots & b \\ b & a_{2}+b & \cdots & b \\ \vdots & \vdots & \ddots & \vdots \\ b & b & \cdots & a_{n}+b \end{vmatrix}$$

$$=\begin{vmatrix} a_{1} & 0 & \cdots & b \\ 0 & a_{2} & \cdots & b \\ \vdots & \vdots & \ddots & \vdots \\ 0 & 0 & \cdots & a_{n}+b \end{vmatrix}+ \begin{vmatrix} a_{1} & b & \cdots & b \\ b & b & \cdots & b \\ \vdots & \vdots & \ddots & \vdots \\ b & b & \cdots & a_{n}+b \end{vmatrix}+ \begin{vmatrix} b & 0 & \cdots & b \\ b & a_{2} & \cdots & b \\ \vdots & \vdots & \ddots & \vdots \\ b & 0 & \cdots & a_{n}+b \end{vmatrix}+ \begin{vmatrix} b & b & \cdots & b \\ b & b & \cdots & b \\ \vdots & \vdots & \ddots & \vdots \\ b & b & \cdots & a_{n}+b \end{vmatrix}=\ldots$$

Note the very last determinant is zero.

For example:

$$\begin{vmatrix}a_1+b&b&b\\ b&a_2+b&b\\ b&b&a_3+b\end{vmatrix}= \begin{vmatrix}a_1&b&b\\ 0&a_2+b&b\\ 0&b&a_3+b\end{vmatrix}+ \begin{vmatrix}b&b&b\\ b&a_2+b&b\\ b&b&a_3+b\end{vmatrix}=$$

$$=\begin{vmatrix}a_1&0&b\\ 0&a_2&b\\ 0&0&a_3+b\end{vmatrix}+ \begin{vmatrix}a_1&b&b\\ 0&b&b\\ 0&b&a_3+b\end{vmatrix}+ \begin{vmatrix}b&0&b\\ b&a_2&b\\ b&0&a_3+b\end{vmatrix}+ \begin{vmatrix}b&b&b\\ b&b&b\\ b&b&a_3+b\end{vmatrix}=\ldots$$

$$=a_1a_2a_3+b(a_1a_2+a_1a_3+a_2a_3)$$

and you were right.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.